Diffusion: macroscale dwarf and nanoscale giant - Nestle, Nikolaus (Diffusion Fundamentals, 2007)
Diffusion processes of particles or energy exhibit a characteristic scaling behavior with space and time. In this contribution, the background of this scaling behavior will be shortly described and its consequences in physics, chemistry, biology and various areas of technology shall be explored. Furthermore, some demonstration experiments for different aspects of diffusion and its scaling behavior will be discussed in the course of the article.